The structure and thermodynamic properties of silicene materials in the cooling process: A new sight from molecular dynamics simulation. (2022) - Van On, Vo; Binh, Tran Thanh
Abstract: This paper presents the results of two-dimensional silicene cooling studies by MD simulation with a sample of 6400 atoms. The Silicene model was run on Lammps software with a Stillinger-Weber interaction potential. Silicene after melting to 3500 K, it is cooled at a rate of 2.10 10 K/s to a temperature of 300 K. Investigation of the dependence of energy on temperature shows a jump in the average total energy of molten silicene at the temperature T = 1965 K. Investigations on the radial distribution function g(r), coordinate number distribution, ring distribution, and angular distribution all show that the freezing temperature of silicene is about 1965 K. When cooled to 300 K, silicene is in crystalline form.